2017
DOI: 10.1007/s11356-017-0313-7
|View full text |Cite
|
Sign up to set email alerts
|

Iron and iron oxide nanoparticles are highly toxic to Culex quinquefasciatus with little non-target effects on larvivorous fishes

Abstract: The control of filariasis vectors has been enhanced in several areas, but there are main challenges, including increasing resistance to insecticides and lack of cheap and eco-friendly products. The toxicity of iron (Fe) and iron oxide (FeO) nanoparticles has been scarcely investigated yet. We studied the larvicidal and pupicidal activity of Fe and FeO nanoparticles against Culex quinquefasciatus. Fe and FeO nanoparticles produced by green (using a Ficus natalensis aqueous extract) and chemical nanosynthesis, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 95 publications
0
9
0
Order By: Relevance
“…This proposes that purification of the extracts is important to enhance the larvicidal activity of compounds. This indicates that bioactivity guided fractionation and purification may lead to the isolation of active chemical compounds responsible for the larvicidal activity [43]. The fractions of P. stratiotes have low activity on Brine shrimp larvae.…”
Section: Fractionsmentioning
confidence: 99%
“…This proposes that purification of the extracts is important to enhance the larvicidal activity of compounds. This indicates that bioactivity guided fractionation and purification may lead to the isolation of active chemical compounds responsible for the larvicidal activity [43]. The fractions of P. stratiotes have low activity on Brine shrimp larvae.…”
Section: Fractionsmentioning
confidence: 99%
“…They were found to be attack Culex quinquefasciatus with negligible off-target impacts on larvivorous fishes. [106] In addition, recent pivotal studies to assess the efficacy of Fe-based NPs to manage plant pathogens. The effect of Fe 3 O 4 NPs on the Tobacco mosaic virus (TMV) confirmed the antiviral potential of these NPs.…”
Section: Nanomaterials For Application In Pesticidesmentioning
confidence: 99%
“…Chemically fabricated nano-iron is being developed as an effective pesticide. It has been shown that iron and iron oxide nanoparticles are highly toxic to Culex quinquefasciatus, the Southern House Mosquito [54].…”
Section: Fig 2 Element Ratios Measured In Filtered Post-spraying Rainwater and Snow From [18] With Permission And With New Rainwater Datamentioning
confidence: 99%